Skewness as a test of dark energy perturbations - Fazolo, Raquel Emy; Amendola, Luca; Velten, Hermano (Physical review, 2022)
We investigate the role played by dark energy perturbations in the skewness S3 of large-scale matter distribution. We consider a two-fluid universe composed by matter and dark energy, with perturbations in both components, and we estimate numerically the skewness of the matter density field as a function of the dark energy parameters. We characterize today’s S3 value for quintessence and phantom dark energy cosmologies as well as its dependence on the matter density parameter Ωm0 and the dark energy sound speed c2s with accurate numerical fitting. These fits can be used to test cosmology against future high quality data on large scale structure.
Gesehen am 27.07.2022